Toward Beyond 3G The FuTURE Project in China. - Xiao-Hu Yu; Guoan Chen; Ming Chen; Xiqi Gao (IEEE Communications magazine)
When research on beyond third generation (B3G) mobile communications had just stepped into its startup period, a project called Future Technologies for a Universal Radio Environment (FuTURE) was launched in China. The goal of the project is to support theoretical research and applicable evaluation of the proposed technologies for B3G mobile communications. In this article the application requirements, technological challenges, and some potential solutions of B3G are discussed, and some key technologies employed in the FuTURE demonstration system are introduced.